Influence of Compensation, Competence, and Discipline on Employee Performance: A Study at RSUD dr. Sayidiman Magetan - David Zola Mandak; Tatik Mulyati; Ahadiati Rohmatiah (Citakonsultindo, 2026)
This research aims to analyze the partial and simultaneous influence of Compensation, Competence, and Discipline on Employee Performance at RSUD dr. Sayidiman Magetan. This study employs a quantitative research design with a sample size of 270 employees. The data analysis techniques utilized include multiple linear regression analysis, t-test (partial), F-test (simultaneous), and the coefficient of determination (R2). The results of the research indicate that: 1) Partially, Compensation, Competence, and Discipline have a significant influence on Employee Performance at RSUD dr. Sayidiman Magetan; 2) Simultaneously, the variables of Compensation, Competence, and Discipline jointly influence Employee Performance at RSUD dr. Sayidiman Magetan; and 3) Discipline is the most dominant variable influencing Employee Performance.